1983
DOI: 10.1021/om50005a015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectra of tetravinyldistibines

Abstract: New tetravinyldistibines, RISbz (where R = vinyl, 16; isopropenyl, 17; l(E)-and 1(Z)-propenyl, 18 and 19; 2-methyl-l-propenyl, 20, and l-methyl-lWpropeny1, 211, have been prepared from the reaction of the corresponding tertiary stibines with active metals in liquid ammonia followed by treatment with 1,2-dichloroethane. While all the distibines show yellow liquid phases, 16 and 17 freeze to violet and orange solids. Compounds 18-21 freeze to yellow solids. 'H NMR, Raman, UV, and mass spectra of 16-21 are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…The diffuse reflectance spectrum of 4hc shows a broad absorption maximum centered at 41b nm, which was distinctly different from that shown by 3b at 350 nm and 3c [9] at 605 nm. Solutions of 3b, 3c and 4bc show only a low intensity shoulder at 346 nm (due to 3c) [4] with end absorption to 420 nm.…”
Section: Attempted Separationcontrasting
confidence: 61%
See 1 more Smart Citation
“…The diffuse reflectance spectrum of 4hc shows a broad absorption maximum centered at 41b nm, which was distinctly different from that shown by 3b at 350 nm and 3c [9] at 605 nm. Solutions of 3b, 3c and 4bc show only a low intensity shoulder at 346 nm (due to 3c) [4] with end absorption to 420 nm.…”
Section: Attempted Separationcontrasting
confidence: 61%
“…It is interesting to compare the absorption maxima shown by the thermochromic solid 4bc, 3c [9] and 3d [13] (see Table 3). Hoffmann et al have suggested that the solid phase color of 3c is due to an u --, r* excitation [14].…”
Section: Attempted Separationmentioning
confidence: 99%
“…Ashe has shown that several distibines (R 2 Sb−SbR 2 ) crystallize in a fashion that aligns the Sb−Sb bonds end to end in an extended structure leading to intensely colored condensed phases. The intermolecular Sb···Sb distances are in the 3.6−3.7 Å range and are considerably shorter than the van der Waals radius separation (4.4 Å).…”
Section: Resultsmentioning
confidence: 99%
“…The M-H bond strength is one factor important in determining the thermodynamics of several interconversions involving metals and hydrocarbon fragments.7 The numerical value of E(FeHFe) reported here has several implications in this regard. For example, E(FeC) and E(FeH) (terminal) suggest that /3-hydrogen elimination (eq 3) on FeCH2CH3 -FeH + C2H4 (3) a mononuclear metal center is an endothermic reaction,20 albeit with a favorable entropy change. In a polynuclear system, the hydride has the possibility of ending up bridging, which will favor the elimination reaction by about another 10-11 kcal/mol (Scheme I).…”
mentioning
confidence: 99%
“…Treatment of a methanol suspension of [Me5CpRhCl2]2 (2) with bubbling CO and an excess of triethylamine at room temperature (eq 3) produced, after 3 h, a deep red-[Me6CpRhCl2]2 + Et3N + CO (1 atm) R°H> 2 Me5CpRh(CO)(COOR)2 + 2Et3N-HCl (3) 3a, R = CH3 3b, R = CH2CH3 orange solution. Evaporation of the solvent in vacuo gave a solid which was extracted with diethyl ether.…”
mentioning
confidence: 99%